Assessments of Functional Cognition Used with Patients following Traumatic Brain Injury in Acute Care: A Survey of Australian Occupational Therapists. Issue 1 (3rd January 2023) - Goodchild, Katherine; Fleming, Jennifer; Copley, Jodie A.
Abstract: This study aimed to describe how occupational therapists working in acute care settings in Australia assess cognitive function in patients with TBI, the influences on assessment choice, and clinician perceptions of performance-based assessment. An online survey was completed by 81 occupational therapists. The most common method of cognitive assessment was reported as non-standardized observation of functional tasks (94.7%), followed by carer-report / self-report (93%). Despite their being positive perceptions of performance-based assessment there was limited use in practice. Assessment use was impacted by practical and organizational constraints including access to assessment resources, time and the built environment in acute care.